2006
DOI: 10.1080/10799890600662595
|View full text |Cite
|
Sign up to set email alerts
|

Safrole-Induced Ca2+Mobilization and Cytotoxicity in Human PC3 Prostate Cancer Cells

Abstract: The effect of the carcinogen safrole on intracellular Ca2+ mobilization and on viability of human PC3 prostate cancer cells was examined. Cytosolic free Ca2+ levels ([Ca2+]i) were measured by using fura-2 as a probe. Safrole at concentrations above 10 microM increased [Ca2+]i in a concentration-dependent manner with an EC50 value of 350 microM. The Ca2+ signal was reduced by more than half after removing extracellular Ca2+ but was unaffected by nifedipine, nicardipine, nimodipine, diltiazem, or verapamil. In C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Previous studies showed that the endoplasmic reticulum is a major Ca 2+ store in most cells [19–21]. Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that the endoplasmic reticulum is a major Ca 2+ store in most cells [19–21]. Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Regarding the Ca 2+ stores involved in MK‐886‐induced Ca 2+ release, our data show that the thapsigargin‐sensitive stores overlapped with MK‐886‐sensitive stores because depletion of the endoplasmic reticulum with thapsigargin fully prevented MK‐886 from releasing more store Ca 2+ , and conversely, MK‐886 pre‐treatment completely depleted thapsigargin‐sensitive stores. Previous studies also have shown that thapsigargin‐sensitive endoplasmic reticulum Ca 2+ store is the dominant store in PC3 cells, by using other agonists such as desipramine [19] and safrole [20]. Furthermore, it seems that phospholipase C‐dependent pathways did not play a role in MK‐886‐induced Ca 2+ release, because the response was not altered by suppressing phospholipase C activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the endoplasmic reticulum (ER) is the major Ca 2+ store in PC3 cells (Chang et al, 2006(Chang et al, , 2008. Figure 4A shows that treatment with 30 μM of celecoxib for 440 seconds induced a [Ca 2+ ] i rise of 52 ± 2 nM, followed by a decay to near baseline.…”
Section: Internal Ca 2+ Stores For Celecoxib-induced Ca 2+ Releasementioning
confidence: 91%
“…The inositol 1,4,5-trisphosphate (IP3)-sensitive Ca 2+ store is an important Ca 2+ store that releases Ca 2+ into the cytosol when cells are stimulated by endogenous ligands, such as histamine (Lee et al, 2001). But, exogenous ligands can release Ca 2+ from inositol IP3insensitive stores (Chang et al, 2006(Chang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation